Material witness eaudiobook - Chapman, Vannetta (Shipshewana Amish Mystery, 2012)
Tragedy strikes on the opening night of the Fall Crafters Fair when a woman is killed in the parking lot of Daisy's Quilt Shop, and the only material witness is one of Melinda Byer's boys. The investigation takes a more bizarre turn when detective Shane Black becomes convinced the killer was actually after Callie. This time it's a madman loose in the largest crowd of the year, and he's looking for something or someone. If they can't figure out what, one of Deborah and Callie's close circle of friends may be next. Masked identities, antique quilts with hidden messages, an Amish boy whose handicap makes him stronger, one brave dog, and a possible hidden treasure ... this time it's nonstop action, danger, and a dash of romance.